PENGARUH ECO-EFFICIENCY TERHADAP NILAI PERUSAHAAN DIMODERASI OLEH KINERJA LINGKUNGAN DALAM PERSPEKTIF EKONOMI ISLAM - Sutjiati, Rhesmita; Ekawati, Evi; Sisdianto, Ersi (Universitas Islam Negeri Alauddin Makassar, 2025)
In the current competitive market, organizations need to manage financial success alongside their social and ecological duties to create businesses that can last. Eco-efficiency serves as a strategic approach to simultaneously manage environmental impacts efficiently and enhance economic performance. However, implementation among JII70-listed companies faces challenges, particularly the absence of consistent mandatory sustainability reporting in Indonesia. This research utilizes quantitative techniques, examining secondary information from the yearly reports and sustainability documents of JII70 firms from 2020 to 2023. With purposive sampling, a total of 11 businesses were chosen, resulting in 44 observations. The analysis of the data was performed using Eviews 12. The results suggest that eco-efficiency has a positive effect on the value of firms, whereas environmental performance does not play a moderating role in this connection. From an Islamic perspective, environmental preservation remains obligatory as ordained in Surah Ar-Rum (30:41).